2017
DOI: 10.1159/000477541
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Hereditary Angioedema Attacks in Children Using Cinryze®: Interim Efficacy and Safety Phase 3 Findings

Abstract: Background: Hereditary angioedema (HAE) is a rare genetic disease causing unpredictable and potentially life-threatening subcutaneous and submucosal edematous attacks. Cinryze® (Shire ViroPharma Inc., Lexington, MA, USA), a nanofiltered C1 inhibitor (C1-INH), is approved in Europe for the treatment, preprocedure prevention, and routine prophylaxis of HAE attacks, and for the routine prophylaxis of attacks in the USA. This phase 3 study assessed the safety and efficacy of 2 C1-INH doses in preventing attacks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The study's safety findings are generally consistent with those in the interim analysis and with pediatric and adult subgroups in other C1‐INH studies …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The study's safety findings are generally consistent with those in the interim analysis and with pediatric and adult subgroups in other C1‐INH studies …”
Section: Discussionsupporting
confidence: 83%
“…In this first blinded, randomized, controlled trial of C1‐INH for prophylaxis targeting patients aged 6‐11 years, the interim analysis in six patients showed that both doses reduced the monthly number of attacks by a mean of 1.89 compared with the BOP . In the complete study described here, mean (percentage) reduction in monthly number of attacks relative to the BOP was 2.58 (71.1%) with 500 U C1‐INH and 2.98 (84.5%) with 1000 U C1‐INH.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Recently, the efficacy and safety of Cinryze, a nano-filtered human plasma-derived C1-INH, has been proven in children with HAE [80]. …”
Section: The Diagnostic Abc For Aementioning
confidence: 99%